Dinner with Mugabe the untold story of a freedom fighter who became a tyrant - Holland, Heidi (Melbourne Bolinda, 2011)
At a time when the world waits anxiously to see what will happen next in Zimbabwe - when there is little food in the country's shops, life expectancy is plunging and Zimbabweans are fleeing repression and unemployment - this book gets to grips with the man at the helm of a corrupt regime; the man behind the monster. Holland's tireless investigation begins with her having dinner with Mugabe the freedom fighter and ends in a searching interview with Zimbabwe's president in December 2007, more than 30 years later.
An unabridged production